Evaluation of Lentil Genotypes (Lens culinaris Medikus) for Growth and Yield Performances across Climate Conditions of Central Highlands of Ethiopia - Nano Alemu Daba; Eba Muluneh Sorecha (Turkish Journal of Agriculture: Food Science and Technology)
Lentil crop has largely been affected by global climate changing, particularly, due to rainfall and temperature changing and variability. Hence, the experiment was conducted in Central Highlands of Ethiopia, namely Akaki, Chefe Donsa and Bishoftu Agricultural Research Centre, in the 2009 and 2010 cropping seasons to assess the genotypic variation of lentil for growth and yield performances. Five lentil genotypes viz. 87S-93549 X EL-103-16, 87S-93549 X EL-103-9-1, Alemaya X FLIP 88-41L-02-AK-14, Alemaya X FLIP 88-41L-02-AK-6 were arranged in randomized complete block design with four replications at all locations. The result of study revealed that the genotype 87S-93549 X EL-103-9-1 produced the highest seed yield of 1985.90 and 2500.00 kg ha-1 during 2009 and 2010 cropping seasons, respectively, at Akaki. On the other hand, the genotype Alemaya X FLIP 88-41L-02-AK-14 gave the highest seed yield (4189.1 kg ha-1) at Chefe Donsa in 2009 cropping season. The genotype X FLIP 88-41L-02-AK-14 was found to be the earliest in physiological maturity, accounting 128.75 days, and the genotype 87S-93549 X EL-103-9-1 had yield advantage of 27.6% over the local check at Chefe Donsa in the 2010 cropping season. Generally, all lentil genotypes were performed better at Chefe Donsa, followed by at Akaki and Bishoftu locations during both cropping seasons. Rainfall and temperature conditions have enormous influences on the growth and yields performances of lentil genotypes at all research locations. The study inspires other studies to be conducted on other factors than climate events thwarting the production of lentil crops in the study areas.